(untitled) (Research, Society and Development, 2020)
This study aimed to relate dietary and water intake with nutritional status and dietary recommendations of elderly residents in public and private Long-Term Care Institutions for Elderly in the hinterland of Rio Grande do Sul. This was a quantitative and cross-sectional study, with 245 elderly. A 24-hour food recall questionnaire was applied to evaluate the amount of water, total calories, macronutrients, and fibers consumed, which was calculated using the DietWin® software (version 2969/2008). The mean macronutrients, fibers and water intake found in this population was compared to the reference values of the Dietary References Intakes. The body Mass Index (BMI) was calculated through weight and height, being the nutritional status classified according to the Pan American Health Organization parameters. The software Package for the Social Sciences (SPSS) version 22.0 was used for statistical analysis. The results considered maximum significance level of 5% (p≤ 0.05). A positive and significant association was found between the total calories consumption and carbohydrates with BMI (r=0.165 and p=0.010; r=0.163 and p=0.011), respectively. The consumption of total calories (p=0.007) and carbohydrates (p=0.006) among the elderly with low weight were significantly lower when compared to the elderly classified with eutrophy, overweight and obesity. Daily water consumption was inversely and significantly associated with age (r=0.168 and p=0.008). It was concluded that the higher the BMI significantly higher was the consumption of total calories and carbohydrates, this consumption being significantly lower among the elderly with low weight.